Nilai Kearifan Lokal Kesenian Bantengan dalam Implementasi Akuntansi - Sopanah, Ana; Hermawati, Adya; Bahri, Syamsul; Utami, Riski Nur; Sulistyan, Riza Bahtiar (Universitas Muhammadiyah Malang, 2024)
Research objective: This study aims to explore local wisdom in Bantengan art and analyze accounting records of transactions that occur during the implementation of Bantengan art. Method/approach: The type of method used is a qualitative method with an ethnomethodological approach, where the author analyzes a culture in the form of the art of